IMPLEMENTASI KEBIJAKAN KARTU INDONESIA SEHAT DI RUMAH SAKIT UMUM DAERAH MANEMBO-NEMBO BITUNG - KAYUWATU, CHELSEA (Sam Ratulangi University, 2020)
There are still many people who deserve free health services can not receive assistance based on problemsthen this research aims to know the implementation of the policy of Indonesia healthy card in the publichospital Manembo District-Nembo BitungThis research is a qualitative research that is a type of research that gives an overview of the description ofa situation on the object studied. The number of research informant 8 persons selected has the criteria forthe information obtained useful for the research conductedThe results showed that the benefits of healthy Indonesian cards are very perceived by the communityespecially for those who have been admitted to the General Hospital Manembo-Nembo district. Bitung.Quality of government apparatus in Bitung City is not fully able to support the implementation of policiesor implementation of Indonesia Sehat card program because there are many complaints of people in theservice when they are hospitalized or puskesmas, there is still discrimination in service by health workers.The structure and mechanism of procedure in implementing the Indonesian Healthy Card program goeswell with the clear standard of work following the technical instructions and implementing organizationsare well coordinated.Keywords: policy implementation, healthy Indonesia card